2008
DOI: 10.1038/nature06381
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced thermoelectric performance of rough silicon nanowires

Abstract: Approximately 90 per cent of the world's power is generated by heat engines that use fossil fuel combustion as a heat source and typically operate at 30-40 per cent efficiency, such that roughly 15 terawatts of heat is lost to the environment. Thermoelectric modules could potentially convert part of this low-grade waste heat to electricity. Their efficiency depends on the thermoelectric figure of merit ZT of their material components, which is a function of the Seebeck coefficient, electrical resistivity, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

91
3,074
5
16

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 3,837 publications
(3,229 citation statements)
references
References 24 publications
91
3,074
5
16
Order By: Relevance
“…[7][8][9] As such, Si NWs have been used in a broad range of applications including nanoelectronics, 10-12 nanosensors, 13 nanoresonators, 14 light-emitting diodes, 15 and thermoelectric energy scavengers. 7,8 The operation and reliability of these nanodevices depend on the mechanical properties of Si NWs, which are expected to be different from their bulk counterparts due to their increasing surface-to-volume ratio.Existing techniques for measuring the mechanics of individual NWs include observing the vibration (or resonance) of cantilevered NWs inside a transmission or scanning electron microscope (TEM/SEM), [16][17][18] measuring the lateral bending of suspended NWs with an atomic force microscope (AFM), 3,19-21 measuring uniaxial tension of suspended NWs in SEM or TEM, 2,22-26 and nanoindentation of NWs on a substate. 27 Available experimental results on Si NWs exhibit significant scatter including the following: (1) some reported a decrease in Young's modulus with decreasing size, 2,9,24,28 while others showed an opposite trend; 20,21 (2) the reported strength values of vapor-liquid-solid (VLS) grown Si NWs ranged from 500 MPa to 12 GPa; 3,28 (3) Han et al 2 observed pronounced plastic deformation of Si NWs by in situ TEM tensile tests at room temperature, while Gordon et al 21 reported linear elastic behavior followed by brittle fracture using AFM bending tests.…”
mentioning
confidence: 99%
“…[7][8][9] As such, Si NWs have been used in a broad range of applications including nanoelectronics, 10-12 nanosensors, 13 nanoresonators, 14 light-emitting diodes, 15 and thermoelectric energy scavengers. 7,8 The operation and reliability of these nanodevices depend on the mechanical properties of Si NWs, which are expected to be different from their bulk counterparts due to their increasing surface-to-volume ratio.Existing techniques for measuring the mechanics of individual NWs include observing the vibration (or resonance) of cantilevered NWs inside a transmission or scanning electron microscope (TEM/SEM), [16][17][18] measuring the lateral bending of suspended NWs with an atomic force microscope (AFM), 3,19-21 measuring uniaxial tension of suspended NWs in SEM or TEM, 2,22-26 and nanoindentation of NWs on a substate. 27 Available experimental results on Si NWs exhibit significant scatter including the following: (1) some reported a decrease in Young's modulus with decreasing size, 2,9,24,28 while others showed an opposite trend; 20,21 (2) the reported strength values of vapor-liquid-solid (VLS) grown Si NWs ranged from 500 MPa to 12 GPa; 3,28 (3) Han et al 2 observed pronounced plastic deformation of Si NWs by in situ TEM tensile tests at room temperature, while Gordon et al 21 reported linear elastic behavior followed by brittle fracture using AFM bending tests.…”
mentioning
confidence: 99%
“…show near linear temperature dependence of thermal conductivity at cryogenic temperatures. [20][21][22] Equation 1 is solved to obtain the temperature profile along the nanowire for an applied V sd assuming the contacts are in thermal equilibrium with the bath temperature (T (x) = T b for x = 0, L). The temperature profile along the nanowire can be analytically written as:…”
mentioning
confidence: 99%
“…11,17,32,57 In a completely unrelated application, galvanic displacement of silver nanoparticles on silicon can be used to etch silicon nanowire arrays in a wet chemical fashion. 58 Although gold-on-silicon nanostructures, prepared by galvanic displacement, have been used in the fabrication of many device architectures, the AuϪSi interface is not well understood, and is the source of much interest. A detailed understanding of the nature and the structure of the goldϪsilicon interface as prepared by galvanic displacement, and the subsequent growth mode of the gold nanostructures merits detailed consideration not only from a technological perspective, but also to elucidate fundamentals in interfacial nanoscience.…”
mentioning
confidence: 99%